The syndrome of transient headache and neurologic deficits with cerebrospinal fluid lymphocytosis (HaNDL): a description of three patients - A. A. Kulesh; N. L. Starikova; V. E. Drobakha; L. Yu. Brokhin; A. S. Chubarov (Неврология, нейропсихиатрия, психосоматика, 2020)
Three clinical cases of the syndrome of transient headache and neurologic deficits with cerebrospinal fluid lymphocytosis (HaNDL) are first described in Russian literature. The patients were young (aged 30–35 years), had symptoms characteristic of the prodromal period of infections. In all the patients, the disease started with intense headache, followed by focal neurological symptoms: aphasia and hemihypesthesia in all cases and confusion with psychomotor agitation in two cases. All the three patients showed spontaneous recovery within 2–3 days. Perfusion computed tomography, magnetic resonance imaging, and electroencephalography are compared in one of the cases. The differential diagnosis of HaNDL with acute cerebrovascular accident, herpetic encephalitis, epilepsy, and migraine is discussed.